Positive electrode lithium supplement agent and preparation method thereof, positive electrode material and lithium ion battery
By introducing flux and inert coating material into the preparation of positive electrode lithium replenishment agent, the particle size and shape are controlled, solving the problem of gas generation deterioration during the use of positive electrode lithium replenishment agent, and improving the electrical performance and processing performance of lithium-ion battery.
Patent Information
- Application Number
- CN202510925905.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-11-21
AI Technical Summary
The positive electrode lithium replenishment agent is prone to gas production deterioration during use, mainly due to the release of oxygen to oxidize the electrolyte during delithiation and the structural cracks caused by deep delithiation, which in turn lead to gas production.
In the preparation process of positive electrode lithium replenishment agent, a flux is introduced. By controlling the sintering temperature and particle size, spherical particles with a single crystal particle size of 3.5 to 5.5 μm are prepared to reduce polarization and particle agglomeration. An inert coating material is used for coating to reduce the contact area between the active material and the electrolyte.
It improves lithium-ion utilization, reduces gas production, enhances battery cycle life and energy density, and improves battery processing and electrical performance.
Smart Images

Figure CN120987377A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular to a positive electrode lithium supplementing agent, a preparation method thereof, a positive electrode material and a lithium ion battery. BACKGROUND
[0002] The positive electrode lithium supplementing agent is a key functional component in the positive electrode material of a battery. Its principle is to introduce an active lithium source into the electrode material in advance during the manufacturing stage of the battery to offset the lithium loss caused by factors such as the formation of a solid electrolyte interface (SEI film) and the decomposition of electrolyte, thereby improving the first coulomb efficiency and overall capacity retention rate of the battery and significantly improving the energy density and cycle life of the battery. It has gradually become an important technical means for advanced battery systems such as high-nickel ternary and silicon-based negative electrodes.
[0003] In actual application, the positive electrode lithium supplementing agent is prone to produce gas deterioration during use. The main reasons are as follows: on the one hand, based on the intrinsic structure of the positive electrode lithium supplementing agent, oxygen is usually released during the delithiation process, and the oxygen released by the positive electrode will oxidize the electrolyte, and the byproduct will migrate to the negative electrode to cause reduction reaction and deteriorate the gas production; on the other hand, the uneven body stress caused by the deep delithiation of the positive electrode lithium supplementing agent causes the positive electrode material to further produce structural cracks, thereby exposing a large number of uncoated fresh interfaces, leading to electrolyte enrichment and decomposition to build a positive electrode electrolyte interface (CEI film) and produce gas. SUMMARY
[0004] The technical problem to be solved by the present application is to improve the problem that the positive electrode lithium supplementing agent is prone to produce gas deterioration during use.
[0005] To solve the above problems, the present application provides a positive electrode lithium supplementing agent, a preparation method thereof, a positive electrode material and a lithium ion battery.
[0006] As a first aspect, the present application provides a preparation method of a positive electrode lithium supplementing agent, comprising: dissolving a fluxing agent and a lithium supplementing agent raw material in a solvent, heating and mixing uniformly, drying to obtain a raw material mixture; sintering the raw material mixture to obtain a first sintered material; wherein the particle size of the single crystal particles of the first sintered material is 3.5 to 5.5 μm; coating the first sintered material to obtain a positive electrode lithium supplementing agent.
[0007] Optionally, the lithium supplementing agent raw material comprises a lithium source, a transition metal, a complexing agent and a metal additive, and the addition amount of the fluxing agent is 0.3 to 3 wt% based on the total mass of the lithium source and the transition metal.
[0008] Optionally, the fluxing agent is selected from one or more of LiOH, LiNO3, LiF, LiCl, LiBO2 and H3BO3. and / or, the metal additive comprises one or more of Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, ZrO2, Li2ZrO3, Co(OH)2, Co3O4, LiCoO2, TiO2, Li4Ti5O 12 and / or, the transition metal comprises one or more of a Fe source, a Ni source, a Co source, and a Mn source. and / or, the metal additive comprises one or more of Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, ZrO2, Li2ZrO3, Co(OH)2, Co3O4, LiCoO2, TiO2, Li4Ti5O
[0009] Optionally, the sintering temperature of the raw material mixture is 250-750°C.
[0010] Optionally, the sintering of the raw material mixture to obtain the first sintered material comprises: sintering the raw material mixture at a first sintering temperature and a second sintering temperature in sequence to obtain the first sintered material; wherein the first sintering temperature is lower than the second sintering temperature, the first sintering temperature is 250-600°C, and the second sintering temperature is 600-750°C.
[0011] Optionally, the coating of the first sintered material to obtain the positive electrode lithium supplementing agent comprises: mixing the first sintered material with an inert coating material and sintering at a third sintering temperature to obtain a second sintered material; electronically conducting coating the second sintered material to obtain the positive electrode lithium supplementing agent.
[0012] Optionally, the inert coating material comprises one or more of Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, TiO2, ZrO2, and SiO2. and / or, the third sintering temperature is 300-500°C.
[0013] As a second aspect, the present application provides a positive electrode lithium supplementing agent prepared by the preparation method of the positive electrode lithium supplementing agent as described in the first aspect.
[0014] As a third aspect, the present application provides a positive electrode material comprising the positive electrode lithium supplementing agent as described in the second aspect, or comprising the positive electrode lithium supplementing agent prepared based on the preparation method of the positive electrode lithium supplementing agent as described in the first aspect.
[0015] As a fourth aspect, the present application provides a lithium ion battery comprising the positive electrode material as described in the third aspect.
[0016] The beneficial effects of the present application compared to the prior art include: This invention introduces a flux during the preparation of the lithium supplement, thereby lowering the crystal nucleation and growth temperature while maintaining or increasing the single-crystal crystallinity. This results in a single-crystal particle size distribution within a reasonable range (3.5 to 5.5 μm) and more regular particle size, reducing polarization caused by excessive particle growth and irregular shape, and preventing Li... + The excessively long extraction path promotes the extraction of lithium ions from the lithium replenisher, ensuring that Li-ion extraction occurs during the first cycle. + Fully delithiated to avoid slow delithiation later on, which could lead to the formation of the initial SEI film and thus increase the Li content in the lithium replenisher. + This improves the utilization rate and mitigates the oxygen release and gas generation issues caused by lithium removal from the lithium replenishing agent in the later stages. Simultaneously, the introduction of a co-solvent can also improve the sphericity of single-crystal particles, enhance the degree of particle dissociation after pulverization, reduce particle agglomeration, and increase the dispersion of single-crystal particles. Increased sphericity helps improve the flowability of single-crystal particles, increases the packing density between materials, increases the contact area between materials, and reduces the contact area between particles and the electrolyte, thereby further reducing gas generation. Attached Figure Description
[0017] Fig. 1 This is a SEM image of the positive electrode lithium replenishing agent prepared in Example 1 of the present invention; Fig. 2 This is a SEM image of the positive electrode lithium replenishing agent prepared in Comparative Example 1 of the present invention; Fig. 3 This is a SEM image of the positive electrode lithium replenishing agent prepared in Comparative Example 2 of this invention. Detailed Implementation
[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0019] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in the description of this application is for the purpose of describing particular embodiments only and is not intended to limit this application. The term "comprising" and its variations as used herein are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the description below. It should be noted that the concepts of "first," "second," etc., mentioned in this invention are used to distinguish different objects, not to describe a specific order or hierarchy. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, unless otherwise stated, "a plurality of" means two or more.
[0020] Lithium replenishers are key materials used in lithium-ion batteries. Their principle is to replenish the gradually depleted lithium ions in the battery by supplying them with additional lithium ions. In a lithium-ion battery, an electrochemical reaction occurs between the positive and negative electrodes. The positive electrode material (such as lithium iron phosphate, lithium manganese oxide, and lithium cobalt oxide) releases lithium ions, which are then embedded into the crystal structure of the negative electrode material (usually graphite). As lithium ions transfer from the positive to the negative electrode, the battery generates current. During the initial charge and discharge of a lithium-ion battery, a solid electrolyte interphase (SEI) film forms on the surface of the negative electrode. The formation of the SEI film requires a large amount of lithium ions. As usage time increases, lithium ions gradually transfer from the positive to the negative electrode, leading to a decrease in battery capacity. At this point, lithium replenishers are needed to provide additional lithium ions, allowing the battery to continue operating normally.
[0021] Lithium replenishing agents include positive electrode lithium replenishing agents, negative electrode lithium replenishing agents, and electrolyte lithium replenishing agents. Positive electrode lithium replenishing agents are present in positive electrode materials (such as lithium iron phosphate, ternary materials, and lithium cobalt oxide), and have advantages such as good process compatibility, direct mixing with positive electrode materials, and easier large-scale production. Positive electrode lithium replenishing agents are typically composed of lithium salt solutions, such as lithium sulfate or lithium phosphate. Taking Li5FeO4 as an example, this positive electrode lithium replenishing agent undergoes the following oxidation reaction during the first charge: Li5FeO4→Fe + 2Li2O + Li + +e − +O2↑ As shown in the above reaction formula, after the lithium ions released by the positive electrode lithium replenisher enter the electrolyte, they are re-intercalated into the crystal lattice of the negative electrode material, thereby replenishing the lithium consumed by the SEI film. In this way, the battery capacity is restored, and it can continue to release current.
[0022] However, based on the intrinsic structure of the positive electrode lithium replenisher, its delithiation process is usually accompanied by oxygen release. The oxygen released from the positive electrode oxidizes the electrolyte, and byproducts migrate to the negative electrode to undergo reduction reactions, worsening gas production. On the other hand, deep delithiation of the lithium replenisher easily leads to bulk stress unevenness, resulting in structural cracks and exposing a large amount of uncoated fresh interfaces. This causes the electrolyte to accumulate and decompose, forming the positive electrode electrolyte interphase (CEI) film and generating gas. Furthermore, high temperatures further drive the overactivation and escape of oxygen in the lithium replenisher. The escape of oxygen disrupts the coordination environment of TM-O, causing the metal to dissolve in the electrolyte and then migrate to the negative electrode to undergo reduction, disrupting the decomposition process of the SEI film and consuming Li. + This, along with the electrolyte, leads to an increase in gas production.
[0023] The preparation methods of positive electrode lithium supplements mainly include coprecipitation, solid-phase method and sol-gel method. Among them, the core of the coprecipitation method is to form a precursor by controlling the coprecipitation process of metal salt solution, and then synthesize the target product through calcination, surface coating and other processes.
[0024] In the preparation of lithium-ion additives for cathodes, preparation parameters such as sintering temperature and particle size of the additive material all affect gas generation during use. Firstly, due to the lithium-rich nature of the additive itself, to ensure its crystallinity and high purity, its sintering temperature is relatively high and the temperature range is narrow. This easily leads to larger particle size and hardness after sintering, resulting in difficulties in controlling particle size and crushing. Furthermore, when the single-crystal particle size of the additive material is too large, Li... + A longer delithiation path can lead to increased material polarization, resulting in incomplete initial delithiation and subsequent continuous delithiation during cycling or storage. During this process, some oxygen in the lithium replenisher participates in charge compensation, causing lattice oxygen release and exacerbating the cathode oxidation reaction, leading to gas generation. Conversely, if the single crystal particle size is too small, the material's specific surface area becomes too large, increasing the contact area between the electrode material and the electrolyte, which also accelerates electrolyte decomposition and gas generation.
[0025] This invention provides a method for preparing a positive electrode lithium supplement, the method comprising the following steps: Step S1: Dissolve the flux and lithium supplement raw materials in a solvent, heat and mix evenly, and dry to obtain a raw material mixture; Step S2: Sinter the raw material mixture to obtain a first sintered material, wherein the single crystal particles of the first sintered material have a particle size of 3.5 to 5.5 μm; Step S3: Coat the first sintered material to obtain the positive electrode lithium replenishment agent.
[0026] This invention introduces a flux into the co-precipitation preparation process of the positive electrode lithium replenisher, allowing the material to melt below its melting point and crystallize under normal pressure. This achieves precise control over the size of single crystal particles in the lithium replenisher material while increasing the sphericity of the single crystal particles, resulting in single crystal particle sizes between 3.5 and 5.5 μm, such as 3.5 μm, 4 μm, 4.5 μm, 5 μm, and 5.5 μm. By introducing a flux during the lithium replenisher preparation process, the crystal nucleation and growth temperature is lowered, while the single crystal crystallinity remains unchanged or even increases. The micro-size and macro-particle size of the sintered material are both reduced, and the grinding intensity required to achieve the target particle size distribution decreases. Therefore, the sphericity of the single crystal particles obtained after grinding is significantly improved. The optimization of the micro-size and macro-particle size of the lithium replenisher and the improvement in sphericity help alleviate the problem of oxygen release and gas generation during use, thereby improving the processing and electrical performance of the lithium replenisher in lithium-ion battery applications.
[0027] Specifically, in the first aspect, the embodiments of the present invention, through the combined control of flux and sintering temperature, ensure that the single crystal particle size distribution of the lithium supplement is within a reasonable range, reducing particle agglomeration, making the particles more regular, reducing polarization caused by excessive particle growth and irregular shape, and avoiding Li + An excessively long extraction path promotes the extraction of lithium ions from the lithium replenisher. This ensures that Li ions are extracted during the first cycle. + Fully delithiated to avoid slow delithiation later on, which could lead to the formation of the initial SEI film and thus increase the Li content in the lithium replenisher. + This improves the utilization rate and reduces the oxygen release and gas generation problem caused by lithium removal from the lithium replenishing agent in the later stage. It also avoids the phenomenon that excessively small single crystal particle size increases the contact area between the electrode material and the electrolyte, thereby accelerating the decomposition of the electrolyte and generating gas.
[0028] On the other hand, the introduction of flux also helps increase the sphericity of the lithium replenishing agent material. Increased sphericity improves the fluidity of single-crystal particles, mitigating the problem of difficulty in forming tight particle packing due to the large size difference between the particles and the cathode material. This contributes to the uniformity of electrode coating and reduces the proportion of particle breakage during electrode rolling due to poor slurry dispersion. Simultaneously, it promotes the uniformity of isotropic stress distribution in the particles, reducing volume expansion and particle breakage rates, thereby mitigating particle breakage caused by deep delithiation of the lithium replenishing agent and reducing the exposure of the electrode active material in the electrolyte. Furthermore, compared to irregular particles, particles with high sphericity can effectively shorten the Li-C ... + Migration distance, reducing Li +Diffusion resistance improves the degree of particle dissociation after pulverization, reduces particle agglomeration, and increases the dispersion of single crystal particles. Furthermore, increased sphericity also helps to increase the packing density between materials, improve electrode compaction, increase the contact area between materials, and reduce the contact area between particles and the electrolyte, thereby reducing gas production. Finally, increased sphericity also enables the active material to form a uniform, complete, and thinner CEI layer, reducing ohmic resistance and the Li-induced thickening caused by repeated film formation. + Consumption and gas production.
[0029] In some optional embodiments, further, in step S1 above, the median particle size of the first sintered material is 8 to 12 μm, for example, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, etc. It should be understood that the single-crystal particle size of the first sintered material refers to the size of its individual crystal particles, which can be specifically determined by scanning electron microscopy (SEM) or X-ray diffraction (XRD). Therefore, the single-crystal particle size can reflect the size characteristics of the material at a microscopic level. The median particle size D50 of the first sintered material represents the value in which 50% of the particles in the macroscopic particle group of the first sintered material have a particle size less than or equal to this value, and the other 50% have a particle size greater than or equal to this value; that is, the median value of the particle group's particle size distribution, reflecting the concentration trend of particle size. Specifically, it can be determined by methods such as laser particle size analysis, sedimentation, and sieving.
[0030] In some optional embodiments, in step S1 above, the lithium replenishing agent raw materials include a lithium source, a transition metal and a metal additive, and may also include a complexing agent, and the amount of flux added is 0.3 to 3 wt% based on the total mass of the lithium source and the transition metal.
[0031] Specifically, in lithium supplement raw materials, the lithium source is Li + In addition to the above, transition metals are mainly used to improve the conductivity and stability of lithium supplements. Complexing agents in lithium supplements play a role in stabilizing lithium ions. By forming complexes with lithium ions, they can prevent direct reactions of lithium ions in the electrolyte and reduce side reactions. Metal additives, through bulk doping, can further stabilize the crystal structure, increase MO bond energy, suppress oxygen evolution at high temperatures, or expand the Li bond through lattice distortion. + Diffusion channels improve ionic conductivity.
[0032] Furthermore, in this embodiment of the invention, the amount of flux is determined based on the total mass of the lithium source and the transition metal, and can be reasonably adjusted according to the actual selection of the lithium source and the transition metal. For example, the amount of flux added can be 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, or 3wt%.
[0033] In some optional embodiments, the flux is selected from one or more of LiOH, LiNO3, LiF, LiCl, LiBO2, and H3BO3. In the lithium supplement raw material, the lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, and lithium phosphate; the transition metal is selected from one or more of Fe, Ni, Co, and Mn sources; the complexing agent is selected from one or more of citric acid, sodium ascorbate, polyethylene glycol, polyvinylpyrrolidone, and oxalic acid; and the metal additive is selected from Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, ZrO2, Li2ZrO3, Co(OH)2, Co3O4, LiCoO2, TiO2, and Li4Ti5O. 12 One or more of the following. Among metal additives, Al... 3+ Zr 4+ It can stabilize the crystal structure, increase the MO bond energy, and suppress oxygen evolution at high temperatures. Ti 4+ Co 2+ It can then replace the Fe in the metal site. 3+ Li is expanded by lattice distortion + Diffusion channels improve ionic conductivity.
[0034] Among the transition metals, the Fe source can be selected from one or more of ferrous sulfate, ferrous chloride, ferric nitrate, iron oxide red, or iron(II,III) oxide, ferric acetate, and ferric citrate; the Ni source can be selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate; the Co source can be selected from one or more of cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt carbonate, cobalt oxalate, and cobalt acetate; and the Mn source can be selected from one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese carbonate, manganese oxalate, and manganese citrate.
[0035] In step S1 above, after dissolving the lithium source, transition metal, flux, complexing agent and metal additive in the above organic solvent or water, the mixture can be heated at a temperature of 40 to 90°C to promote uniform mixing of the substances, and then dried to obtain the raw material mixture.
[0036] Specifically, the solvent can be selected from one or more of methanol, glycerol, ethanol, and water. In this embodiment of the invention, a flux is introduced into the lithium replenishment material through liquid-phase mixing, accelerating grain rearrangement and thus inhibiting excessive growth and agglomeration of particles during sintering, which is beneficial for obtaining smaller and more uniform grains. This improves the problems of frequent particle breakage, increased specific surface area, and poor slurry stability during lithium-ion battery processing caused by excessively large single crystal sizes in lithium replenishment materials. Furthermore, the molten flux coating the particle surface helps reduce the high-temperature volatilization of Li2O and O2, effectively improving lithium utilization. In addition, residual flux (such as B and F) forms a passivation layer or doping effect on the particle surface, which also helps suppress electrolyte side reactions (such as HF erosion), reduce interfacial impedance growth, and enhance surface lithium-ion diffusion kinetics.
[0037] In some optional embodiments, in step S2 above, the sintering temperature of the raw material mixture is 250 to 750°C.
[0038] Specifically, the raw material mixture can be sintered sequentially at a first sintering temperature and a second sintering temperature to obtain a first sintered material. The first sintering temperature is lower than the second sintering temperature, with the first sintering temperature being 250 to 600°C and the second sintering temperature being 600 to 750°C. The holding times at the first and second sintering temperatures are 4 to 22 hours, respectively.
[0039] This invention involves a two-stage sintering process for the raw material mixture. The first sintering temperature is selected from 250 to 600°C, for example, 250°C, 280°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, and 600°C. The second sintering temperature is selected from 600 to 750°C, for example, 600°C, 650°C, 680°C, 700°C, and 750°C. The first sintering temperature should be lower than the second sintering temperature. The purpose of the first stage of sintering is to promote the dehydration of the lithium source and transition metals, and the formation of lithium supplements. The second stage of sintering, at a higher temperature, is to promote the inward migration of metal ions, thereby achieving the doping of metal additives.
[0040] It should be understood that the higher the sintering temperature, the larger the single crystal particle size. The size of the single crystal reflects the crystallinity and affects the material's kinetics and processing properties. Therefore, in the actual sintering process of the raw material mixture, in order to finely control the particle size and size distribution of the sintered material, the sintering temperature needs to be finely adjusted according to the choice of flux. Specifically, the single crystal particle size can be measured by measuring the SEM image of the first sintered material, and then combined with the control of the sintering temperature, the single crystal particle size can be controlled within the range of 4.5±1μm.
[0041] In some optional embodiments, step S3, coating the first sintered material to obtain the positive electrode lithium replenishing agent, may include: Step S31: Mix the first sintering material with the inert coating material and sinter at the third sintering temperature to obtain the second sintering material.
[0042] Step S32: Coat the second sintered material with an electronic conductor to obtain a positive electrode lithium replenishing agent.
[0043] This invention employs an inert coating material to sinter and coat the pulverized material. This inert coating material forms a coating layer on the surface of the sintered pulverized material, effectively isolating the active material of the lithium supplement from air. This prevents the active material from directly contacting carbon dioxide and water in the air, thus avoiding the formation of residual alkali that could lead to lithium degradation. + It consumes and affects the material's processing performance. Furthermore, double sintering results in higher material crystallinity, reducing the contact area between the active material and the electrolyte, minimizing interfacial side reactions during charging / discharging or high-temperature storage, thereby avoiding Li... + Loss, and the formation of inactive inert layers, etc.
[0044] In some optional embodiments, the inert coating material is selected from one or more of Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, TiO2, ZrO2 and SiO2.
[0045] In this embodiment of the invention, the inert coating material can be selected from inert metals, such as aluminum, titanium, and zirconium sources, or inorganic materials such as silicon dioxide, thereby forming an oxide or fluoride coating on the surface of the active component to achieve the effect of blocking the electrolyte, reducing the release of surface reactive oxygen species, and inhibiting gas generation. Furthermore, by controlling the composition of the interface SEI film, the polarization voltage can be further reduced.
[0046] In some optional embodiments, in step S31 above, the third sintering temperature is 300 to 500°C.
[0047] Specifically, in this embodiment of the invention, the inert coating material is physically mixed with sintered pulverized material and then sintered at low temperature for coating. In other embodiments, ALD atomic layer deposition can also be used for coating, and materials such as trimethylaluminum and triethylaluminum can be used to obtain a denser, more complete, and thinner coating layer.
[0048] In some optional embodiments, in step S32 above, the electronic conductor can be selected from at least one of the following: carbon layers formed from glucose, sucrose, PEG, graphene, carbon nanotubes, carbon nanofibers, graphite, and carbon black. The electronic conductor coating can be achieved through solid-phase mixing and liquid-phase mixing. Specifically, during solid-phase mixing, the second sintering material can be directly physical-composite with carbon sources such as graphene, carbon nanotubes, carbon nanofibers, graphite, and carbon black at room temperature using a high-speed mixer. It should be noted that the specific steps for electronic conductor coating are well known to those skilled in the art and will not be elaborated here.
[0049] In some optional embodiments, size control can be further performed at multiple stages of lithium supplement synthesis. For example, after obtaining the raw material mixture in step S1, the raw material mixture can be coarsely crushed to reduce the difficulty of subsequent size control; or, in step S2, after sintering the raw material mixture to obtain the first sintered material, the first sintered material can be subjected to air jet milling to further control the particle size and size distribution of the first sintered material, controlling the single crystal particle size of the first sintered material between 3.5 and 5.5 μm and the median particle size D50 between 8 and 12 μm, to obtain a material with higher sphericity and satisfying the particle size distribution. Or, in step S31, after obtaining the second sintered material, the second sintered material can be mechanically pulverized to further control the particle size of the second sintered material coated with inert coating material, concentrating the single crystal particles and median particle size of the second sintered material towards a preset range. By controlling the particle size and size distribution of single crystal particles of each intermediate product in multiple stages of lithium replenishment, it is beneficial to further improve the quality of the finished positive electrode lithium replenishment, so as to compensate for the phenomenon of particle agglomeration and size increase that occurs during the preparation of positive electrode lithium replenishment particles.
[0050] Specifically, optionally, the parameters for airflow milling may include: milling air pressure between 0.65 and 0.85 MPa, induced draft frequency between 35 and 45 Hz, classifier frequency between 45 and 55 Hz, feed rate between 60 and 120 kg / h, and dew point control at -30°C. The parameters for mechanical milling may include: airflow velocity between 300 and 1200 m / s, and feed rate between 1 and 50 kg / h.
[0051] Another embodiment of the present invention provides a positive electrode lithium replenisher, which is prepared using the above-described method for preparing positive electrode lithium replenishers. Specifically, the general formula of the positive electrode lithium replenisher can be Li x M y O z This indicates that M is a transition metal such as Fe, Ni, Co, or Mn. For example, the positive electrode lithium supplement prepared using the preparation method in the embodiments of the present invention can be Li5FeO4, LiNiO2, etc.
[0052] Another embodiment of the present invention provides a positive electrode material, which includes the above-mentioned positive electrode lithium replenishing agent, or includes a positive electrode lithium replenishing agent prepared based on the above-mentioned method for preparing the positive electrode lithium replenishing agent.
[0053] Another embodiment of the present invention provides a lithium-ion battery comprising the above-described positive electrode material.
[0054] The present invention will be described in detail below through specific embodiments and comparative examples: Example 1 The preparation method of the positive electrode lithium supplement in this embodiment includes the following steps: Step 1: Weigh the flux and lithium supplement raw materials according to the specified ratio and dissolve them in water. The lithium source is lithium hydroxide, the transition metal is iron oxide red, the flux is boric acid, the complexing agent is citric acid, and the metal additive is Co(OH)2. The molar ratio of lithium hydroxide to iron oxide red is 5.04:0.5. Based on the total mass of lithium source and M source being 100%, the amount of boric acid added is 1 wt%, the amount of citric acid added is 2 wt%, and the amount of Co(OH)2 added is 1 wt%. Then, heat at 50°C and mix evenly, and finally dry to obtain the raw material mixture.
[0055] Step 2: After coarsely pulverizing the raw material mixture, it is first sintered at 600℃ for 5 hours, followed by a second sintering at 750℃ for 5 hours to obtain the first sintered material. The single crystal particle size of the first sintered material is controlled within the range of 4.5±1μm, and the D50 is controlled within the range of 10±2μm. Then, the first sintered material is subjected to air jet milling to further compensate for the increased particle size caused by agglomeration, controlling the single crystal particle size of the sintered material to remain within the range of 4.5±1μm, and the D50 to remain within the range of 10±2μm. The process parameters for air jet milling are: milling air pressure around 0.8MPa, induced draft frequency of 40Hz, classifier wheel frequency of 45Hz, feed rate of 80kg / h, and dew point control of -30℃.
[0056] Step 3: Mix the sintered pulverized material with Al2O3, wherein the amount of Al2O3 added is 1wt% based on the mass of the sintered pulverized material as 100%, and then sinter at 500℃ to obtain the second sintered material. Further mechanical pulverization is used to control the single crystal particle size of the second sintered material within the range of 4.5±1μm.
[0057] Step 4: Use a high-speed mixer to physically mix the second sintered material with graphene at room temperature to coat the second sintered material with electronic conductors, thereby obtaining the positive electrode lithium replenishing agent.
[0058] Example 2 The difference between this embodiment and Embodiment 1 is that in step one, the lithium source is lithium oxide, the transition metal is iron acetate, the flux is LiOH, the complexing agent is oxalic acid, and the metal additive is ZrO2. The molar ratio of lithium oxide to iron acetate is 2.52:1. Based on a total mass of 100% for both the lithium source and the M source, the amount of LiOH added is 0.3 wt%, the amount of oxalic acid added is 0.5 wt%, and the amount of ZrO2 added is 0.3 wt%.
[0059] In step two, the raw material mixture is first sintered at 400℃ for 15 hours, and then sintered at 650℃ for 15 hours to obtain the first sintered material. Other steps and parameters are the same.
[0060] Example 3 The difference between this embodiment and Embodiment 1 is that in step one, the flux is LiBO2, and the amount of LiBO2 added is 3wt% based on the total mass of lithium source and M source being 100%.
[0061] In step two, the raw material mixture is first sintered at 250℃ for 22 hours, and then sintered at 600℃ for 22 hours to obtain the first sintered material. Other steps and parameters are the same.
[0062] Comparative Example 1 The difference between this comparative example and Example 1 is that the flux boric acid is not added in step one, while the other steps and parameters are the same.
[0063] Comparative Example 2 The difference between this comparative example and Example 1 is that in step one, the flux and lithium supplement raw materials are mixed in a solid phase according to a certain ratio to obtain a raw material mixture.
[0064] Comparative Example 3 The difference between this comparative example and Example 1 is that in step two, the single crystal particle size of the first sintered material is controlled to be <3.5μm by lowering the sintering temperature.
[0065] Comparative Example 4 The difference between this comparative example and Example 1 is that in step two, the single crystal particle size of the first sintered material is controlled to be >5.5μm by increasing the sintering temperature.
[0066] The Li5FeO4 lithium supplementer from Examples 1 to 3 and Comparative Examples 1 to 4 was applied to lithium iron phosphate pouch batteries. The positive electrode slurry ratio was lithium iron phosphate + lithium supplementer: SP:CNTs:PVDF = 97.0:0.9:0.3:1.8. A dispersant was also added to the positive electrode slurry, with an addition amount of 0.05 wt% based on the total mass of the positive electrode slurry. The ratio of lithium supplementer to lithium iron phosphate was 0.8:96.2, and the designed capacity was approximately 3 Ah. Key electrical performance tests were then performed on each battery. The lithium supplementer dimensional parameters and the electrical performance test data for each battery are shown in Table 1. Table 1. Size parameters of lithium replenishment agent and electrical performance test data of each battery.
[0067] It should be noted that, when characterizing the sphericity of the positive electrode lithium replenisher, the sphericity can be quantified as follows: the direction of the farthest distance from the center of the single crystal particle to the particle surface in the SEM planar image of the positive electrode lithium replenisher can be set as the a-axis, and the direction perpendicular to the a-axis can be set as the b-axis. The magnitudes of the a-axis and b-axis are the lengths from the center to the particle surface in the corresponding directions, respectively. It should be understood that when the a / b value is close to 1, the sphericity is better; when the a / b value is greater than 1, the sphericity is worse. For example, the SEM morphology image of the positive electrode lithium replenisher prepared in Example 1 is shown below. Fig. 1 As shown, the SEM morphology images of the positive electrode lithium replenishment agents prepared in Comparative Examples 1 and 2 are as follows: Fig. 2 and Fig. 3 As shown, by Figs. 1 to 3 It can be seen that the sphericity of Example 1 is significantly improved compared with Comparative Examples 1 to 2.
[0068] Table 1 lists the size parameters and related electrical performance parameters of the lithium replenishing agent from top to bottom as follows: single crystal particle size, median particle size, sphericity, DC internal resistance of the battery under constant current discharge or charging at 50% state of charge at room temperature, DC internal resistance of the battery under constant current discharge or charging at 50% state of charge at room temperature, DC internal resistance of the battery under constant current discharge or charging at 50% state of charge at low temperature (5℃), DC internal resistance of the battery under constant current discharge or charging at 50% state of charge at low temperature (5℃), 28-day storage volume change of the battery under 100% state of charge at high temperature (45℃), storage capacity retention rate, and storage capacity recovery rate.
[0069] As shown in Table 1, compared to Comparative Examples 1 to 4, the positive electrode lithium replenishing agents in Examples 1 to 3 exhibit improved sphericity, a / b values closer to 1, and smaller charge-discharge DCRs at both room temperature and low temperature. This indicates that the suitable particle size distribution and superior sphericity of the positive electrode lithium replenishing agent enhance the Li-to-Li ratio in the battery. +A shorter transport path and a higher delithiation depth of the positive electrode lithium supplement result in a better reduction in the SEI film impedance of the negative electrode. Simultaneously, batteries assembled using the positive electrode lithium supplements from Examples 1 to 3 exhibit less volume change and better capacity retention and recovery after 28 days of high-temperature storage. This indicates that the addition of the positive electrode lithium supplements from Examples 1 to 3 improves battery gas production and Li... + Less loss.
[0070] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode lithium supplement, characterized in that, The preparation method of the positive electrode lithium supplement includes: The flux and lithium supplement raw materials are dissolved in a solvent, heated and mixed evenly, and then dried to obtain a raw material mixture; The raw material mixture is sintered to obtain a first sintered material; wherein the single crystal particles of the first sintered material have a particle size of 3.5 to 5.5 μm; The first sintered material is coated to obtain a positive electrode lithium replenishing agent.
2. The method for preparing the positive electrode lithium supplement according to claim 1, characterized in that, The lithium replenishing agent raw materials include a lithium source, a transition metal, and metal additives. The amount of flux added is 0.3 to 3 wt% based on the total mass of the lithium source and the transition metal.
3. The method for preparing the positive electrode lithium supplement agent according to claim 2, characterized in that, The flux is selected from one or more of LiOH, LiNO3, LiF, LiCl, LiBO2 and H3BO3; And / or, the metal additives include Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, ZrO2, Li2ZrO3, Co(OH)2, Co3O4, LiCoO2, TiO2, Li4Ti5O 12 One or more of them; And / or, the transition metal includes one or more of Fe, Ni, Co and Mn sources.
4. The method for preparing the positive electrode lithium replenishing agent according to claim 1, characterized in that, The sintering temperature of the raw material mixture is 250 to 750°C.
5. The method for preparing the positive electrode lithium supplement agent according to claim 4, characterized in that, The step of sintering the raw material mixture to obtain a first sintered material includes: The raw material mixture is sintered sequentially at a first sintering temperature and a second sintering temperature to obtain a first sintered material; wherein the first sintering temperature is lower than the second sintering temperature, the first sintering temperature is 250 to 600°C, and the second sintering temperature is 600 to 750°C.
6. The method for preparing the positive electrode lithium replenishing agent according to claim 1, characterized in that, The process of coating the first sintered material to obtain a positive electrode lithium supplement includes: The first sintering material is mixed with an inert coating material and sintered at a third sintering temperature to obtain the second sintering material. The second sintered material is coated with an electronic conductor to obtain the positive electrode lithium replenishing agent.
7. The method for preparing the positive electrode lithium supplement agent according to claim 6, characterized in that, The inert coating material includes one or more of Al2O3, AlOOH, Al(OH)3, AlF3, LiAlO2, TiO2, ZrO2 and SiO2; And / or, the third sintering temperature is 300 to 500°C.
8. A positive electrode lithium replenishing agent, characterized in that, The positive electrode lithium replenishing agent is prepared by the preparation method of the positive electrode lithium replenishing agent as described in any one of claims 1 to 7.
9. A positive electrode material, characterized in that, The cathode material includes the cathode lithium replenisher as described in claim 8, or includes the cathode lithium replenisher prepared by the method for preparing the cathode lithium replenisher as described in any one of claims 1 to 7.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode material as described in claim 9.